2012
DOI: 10.1097/aln.0b013e31823d7731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glutamate and Blood Glutamate Scavengers Oxaloacetate and Pyruvate on Neurological Outcome and Pathohistology of the Hippocampus after Traumatic Brain Injury in Rats

Abstract: Background: Decreasing blood glutamate concentrations after traumatic brain injury accelerates brain-to-blood glutamate efflux, leading to improved neurologic outcomes. The authors hypothesize that treatment with blood glutamate scavengers should reduce neuronal cell loss, whereas administration of glutamate should worsen outcomes. The authors performed histologic studies of neuronal survival in the rat hippocampus after traumatic brain injury and treatment with blood glutamate scavengers. Methods: Traumatic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…Although the precise mechanisms of pyruvate protection have not been elucidated, preservation of NAD and ATP levels seem to play a key role in normalizing zinc dyshomeostasis (Sheline et al, 2000). Pyruvate and ethyl pyruvate have been shown to have protective effects in animal models of brain ischemia, epilepsy, and brain trauma (Lee et al, 2001;Kim et al, 2007;Yi et al, 2007;Yu et al, 2005;Zlotnik et al, 2012). In addition, pyruvate may increase endogenous zinc chelation through the generation of citrate and isocitrate (unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanisms of pyruvate protection have not been elucidated, preservation of NAD and ATP levels seem to play a key role in normalizing zinc dyshomeostasis (Sheline et al, 2000). Pyruvate and ethyl pyruvate have been shown to have protective effects in animal models of brain ischemia, epilepsy, and brain trauma (Lee et al, 2001;Kim et al, 2007;Yi et al, 2007;Yu et al, 2005;Zlotnik et al, 2012). In addition, pyruvate may increase endogenous zinc chelation through the generation of citrate and isocitrate (unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies done by our group and others have shown that pharmacologically reducing blood glutamate levels with glutamate scavengers (such as oxaloacetate and pyruvate) limit glutamate neurotoxicity and provide better neurologic outcomes after various brain insults, particularly traumatic brain injury [14,[19][20][21][44][45][46][47][48][49][50][51][52][53]. Unfortunately, although these treatments have been shown to be effective in animal models of stroke, traumatic brain injury, and subarachnoid hemorrhage, their use in humans is limited by Food and Drug administration restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is based on the administration of oxaloacetate or recombinant glutamate oxaloacetate transaminase 1 (rGOT1), which leads to a metabolization and reduction of glutamate in blood and a subsequent lowering of glutamate in the cerebral parenchyma (see Campos et al 13 and Teichberg et al 14 for review). The protective efficacy of this strategy has been widely shown by independent laboratories in different types of ischemic animal models, [15][16][17][18][19][20] and it has also been tested in other pathologies associated with brain glutamate increase, such as traumatic brain injury, 21,22 subarachnoid hemorrhage, 23,24 or glioma, 25 with successful results. However, the use of blood glutamate grabbers has never been tested in an ICH model.…”
Section: Introductionmentioning
confidence: 99%